Evaluation of Passenger Transport Services in Bastiong Ferry Port, North Maluku Province - Muhammed Ebuzer Ersoy; Ong Argo Victoria; Fikri Miftahurrahman (IWJ : Inland Waterways Journal, 2019)
Ternate is a city of islands, Ternate is very dependent on the mode of transport crossing that connects the islands in the vicinity. This port is felt more and more important and strategic because it provides an enormous impact on the growth and development of Ternate region because it serves as the entry and exit of goods and staples. Bastiong Ferry Port which is under the authority PT.ASDP Indonesia Ferry (Persero) Branch Ternate. Based on this analysis it was concluded that there are variables that are still lacking in the service of some ferry transport as not Information not available yet and Safety Facility that is easily visible and affordable form of fire extinguishers, manual evacuation routes, and emergency numbers, are not yet available information and existing health facilities but the unavailability of health workers, Waiting Room facilities are not well maintained and dirty, the facilities existing toilets smelling and dirty condition, the unavailability of Advanced Transport Information to users of services, not provided passenger service facilities, unavailability is the availability of a uniformed porter who have an identity and be easily visible, good condition and function makes it easy for passengers to carry luggage, the unavailability of facilities for passengers difable, The management though because it must complete the port operations and improving service facilities on Bastiong ferry ports in accordance with the benchmarks that have been required in the Regulation of the Minister of Transportation Number 39 Of 2015 on Ferry Transport Passenger Service Standards.